1985
DOI: 10.1007/bf00218014
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II-immunoreactive neurons in the caudal neurosecretory system of freshwater and seawater fish

Abstract: Antiserum generated against synthetic urotensin II of the goby, Gillichthys mirabilis, was used to localize urotensin II in the caudal neurosecretory system in six species of freshwater teleosts: Cyprinus carpio, Carassius auratus, Oreochromis mossambicus, Oreochromis niloticus, Salmo gairdneri and Plecoglossus altivelis, and six species of seawater teleosts: Acanthogobius flavimanus, Pagrus major, Parapristipoma trilineatum, Trachurus japonicus, Seriola dumerili and Seriola quinqueradiata. In the carp, uroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
0
20
1
Order By: Relevance
“…The fact that immunoreactive UII appeared to be greater in the urophysis of seawater species versus freshwater species suggested an osmoregulatory role for at least UII (566). This was corroborated by a subsequent study that demonstrated increased immunoreactivity for both UI and UII in the urophysis of freshwater acclimated longjaw mudsucker, but this could be secondary to increased synthesis and storage, decreased release of stored peptide, or decreased peptide degradation (385).…”
Section: Urotensinsmentioning
confidence: 73%
“…The fact that immunoreactive UII appeared to be greater in the urophysis of seawater species versus freshwater species suggested an osmoregulatory role for at least UII (566). This was corroborated by a subsequent study that demonstrated increased immunoreactivity for both UI and UII in the urophysis of freshwater acclimated longjaw mudsucker, but this could be secondary to increased synthesis and storage, decreased release of stored peptide, or decreased peptide degradation (385).…”
Section: Urotensinsmentioning
confidence: 73%
“…The presence of UII-immunoreactivity in the brain of fishes has been controversial (Y. Owada et al, 1985). We could not detect UII mRNA in the carp brain by RNA transfer blot hybridization.…”
Section: Discussionmentioning
confidence: 76%
“…(1) Since the quantity of VII-@, a mixture of equal amounts of 2 components, is about half of either UII-(r or -y (Ichikawa et al, 1984), mRNA encoding either component of VII-/3 might be lower in quantity compared with that of UII-cr or -7. (2) UIIimmunoreactive neurons have been shown to be located in the spinal cord both anterior and dorsal to the urophysis in the carp (Owada et al, 1985). We extracted mRNA from the spinal cord anterior to the urophysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, antisera to the corticotropin-releasing factor (CRF) and sauvagine were successfully used to localize a UI-like substance, since CRF and sauvagine have several amino acid sequences homologous with UI (CRF: LARSON et al, 1984;ONSTOTT and ELDE, 1984;BERN et al, 1985;OWADA et al, 1985b;YAMADA et al, 1985;sauvagine: RENDA et al, 1982). Neurons producing UII were also immunohistochemically located in several species of teleosts (LARSON et al, 1984;OWADA and KOBAYASHI, 1984;BERN et al, 1985;OWADA et al, 1985a;YAMADA et al, 1985) and in elasmobranchs (OWADA et al, 1985b). In these studies, several investigators noted the co-localization of a CRF-or UI-like (CRF/UI) substance and UII in the same neurons in teleosts (LARSON et al, 1984;BERN et al, 1985;YAMADA et al, 1985) and in elasmobranchs (OWADA et al, 1985b As rabbit antiserum to carp UI has recently become available, in the present study we used UI antiserum instead of CRF antiserum to localize UI and also to examine the possible coexistence of UI and UII in the same neurons of the caudal neurosecretory system of the carp and two species of shark.…”
Section: Discussionmentioning
confidence: 99%